Developmental Potential of the Communes of the Lubelskie Voivodship - Szlachta, Jacek; Dziemianowicz, Wojciech; Szmigiel, Katarzyna; Nowicka, Paulina (Regional Barometer. Analyses & Prognoses, 2009)
In the paper, while using 25 factors describing wealth, modernity and competitiveness, two types of typology of the Lubelskie province communes were made: dynamic typology (in 2002-2007) and static typology (in 2007). The most interesting subject matter for regional policy in typology constitutes the communes in which a disproportion between potential and dynamics of development occurs (communes type AB and BA). Carried out typology laid foundation for conclusions and recommendations for inter- and intra-regional policy.